Hubungan Kualitas Pelayanan Keperawatan dengan Kepuasan Pasien di Poli Penyakit Dalam Rumah Sakit Panti Rapih Yogyakarta - Anastasia Mita Rusviani; Hastuti, Agustina Sri Oktri; Mahayanti, Agnes (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Background: Quality service is a health service process which is administered in accordance with service standards and professional code of ethics to provide satisfaction to health service recipients. Quality service will determine the level of patient satisfaction and trust in a hospital. Satisfaction is a feeling of pleasure towards the service received where the service is in accordance with the expectations or exceeds the expectations of the patient. According to Parasuraman, cited by Muninjaya (2011), service quality is determined by five main factors, namely tangible, reliability, assurance, responsiveness, and empathy. Purpose: The purpose of this study was to determine the relationship between the quality of nursing services and patient satisfaction in the Internal Medicine Department of the Panti Rapih Hospital, Yogyakarta. Methods: This research is a quantitative study, the research design used is cross sectional. The population of this study were patients who underwent an examination at the Internal Medicine Department of the Panti Rapih Hospital Yogyakarta with a total sample of 135 respondents who were selected by purposive sampling according to the inclusion criteria. The data were collected using a questionnaire sheet, then the data were analyzed using the Spearman statistical test. Results: The results of service quality test responsiveness with p value 0.091, and empathy with p value 0.862. Tangible quality test results with p value 0,000, reliability with p value 0,000, and assurance with p value 0,000 Conclusion: There is no relationship between service quality (responsiveness and empathy) with patient satisfaction in the Internal Medicine clinic at Panti Rapih Hospital Yogyakarta and there is a relationship between service quality (tangible, reliability and assurance) with patient satisfaction at the Internal Medicine clinic at Panti Rapih Hospital Yogyakarta. Hospitals are advised to maintain service quality by maintaining responsiveness, increasing knowledge, skills, attractive appearance in providing services and caring. Keywords: quality of service dimension, patients’ satisfaction.